1993
DOI: 10.1007/bf00146274
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence to some torch agents in a sicilian female population of fertile age

Abstract: The seroprevalence to Toxoplasma gondii (41.1%), rubella virus (88.2%), cytomegalovirus (86.0%), and herpes simplex virus (80.0%) has been evaluated in fertile women living in Catania (Sicily). The population group studied was divided into four age groups to quantify the risk of primary infection in each age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 7 publications
2
6
0
2
Order By: Relevance
“…In this study, the prevalence of anti-T. gondii antibodies in women of childbearing age from both the Tuscany and Apulia regions is consistent with the declining trend observed in recent decades in other regions in Italy [18,20], as well as in other European countries [2,9,13] and the United States [14]. In Italy, T. gondii prevalence in women of childbearing age was 41.1% in the late 1980's [6], and a trend toward a decrease has become evident since 2001 [20]. This decline in prevalence is correlated to declining incidence, due to lower exposure to the parasite by changes in nutritional habits and by improved hygiene practices in meat production [19].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, the prevalence of anti-T. gondii antibodies in women of childbearing age from both the Tuscany and Apulia regions is consistent with the declining trend observed in recent decades in other regions in Italy [18,20], as well as in other European countries [2,9,13] and the United States [14]. In Italy, T. gondii prevalence in women of childbearing age was 41.1% in the late 1980's [6], and a trend toward a decrease has become evident since 2001 [20]. This decline in prevalence is correlated to declining incidence, due to lower exposure to the parasite by changes in nutritional habits and by improved hygiene practices in meat production [19].…”
Section: Discussionsupporting
confidence: 88%
“…Consequently, no accurate estimates of the impact of toxoplasmosis on the population are available, and epidemiological information on the prevalence of T. gondii infection is incomplete, area-based, and mostly focused on pregnant women [3-5, 7, 8, 23, 24, 26, 28, 30]. Epidemiological data on T. gondii seroprevalence in women of childbearing age are even more scant [6,11,18,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, our data show a lower seropositivity in women of this age group (19.4%) compared with previous studies in other regions of Italy (in the northern, central, and southern Italy) where values higher than 40% were found [25,28,29]. Actually, the Parma area [25] reflects a situation quite similar to ours, both geographically and for socio-economic factors, including food habits.…”
Section: Discussionsupporting
confidence: 50%
“…Anti-CMV IgG seropositivity ranges between 58.7% and 99.5%. 9,11,12,28,31 In studies performed in different regions of our country, however, anti-CMV IgG seropositivity was observed at similar levels, ranging between 98% and 99%. [16][17][18][19]25 No sign of congenital abnormalities was found the amniocentesis group or in the follow-up group in the perinatal period and in postpartum controls.…”
Section: Discussionmentioning
confidence: 85%
“…[16][17][18][19]25 No sign of congenital abnormalities was found the amniocentesis group or in the follow-up group in the perinatal period and in postpartum controls. In the literature comparison of the other studies around the world, Abdel-Fattah et al 5 from the UK, Condorelli et al, 31 Paradhan et al 9 from Nepal and Vilibic-Cavlek et al 11 from Croatia showed that anti-CMV IgG seropositivity in Turkey was rather higher. Although these results showed that screening of anti-CMV antibodies in Turkish women of reproductive age and potential is necessary, the issue of giving priority to providing information about the routes of transmission and protection from CMV infection and symptoms of the acute infection in Turkey during pregnancy instead of screening remains controversial.…”
Section: Discussionmentioning
confidence: 92%